Modified life’s essential 8 mediate the correlation between dietary index for gut microbiota and sleep disorders - Fang, Juanjuan; Wang, Zhenhua; Yu, Jiangshui; Ye, Yumin; Du, Apang; Ferrari, Markus W. (Frontiers in Nutrition, 2025)
BackgroundThe research sought to examine the correlation between the dietary index for gut microbiota (DI-GM) and sleep disorders. The specific relationship between DI-GM and sleep pathophysiology requires further elucidation. Methods: The data were obtained from the National Health and Nutrition Examination Survey (NHANES) across six cycles over the years 2007 to 2018. We applied logistic regression analyses with multivariable adjustments with sample weighting to assess the independent associations of DI-GM, its beneficial and unfavorable subcomponents, with sleep disorders prevalence, reporting effect estimates as adjusted odds ratios (ORs). We used restricted cubic spline (RCS) models to evaluate relationships between dose and response, and subgroup analyses to explore effect modifications. We used mediation analysis to assess the intermediary role of mLE8 (Modified Life’s Essential 8) and all its components.ResultsAfter full adjustment, higher DI-GM and DI-GM beneficial scores were found to be associated with a reduction in sleep disorders (OR: 0.92, 95% CI: 0.86–0.97; OR: 0.90, 95% CI: 0.85–0.96, respectively). Individuals whose DI-GM was 5 or above had a 34% decreased chance of sleep disorders compared to those with scores of 3 or less (OR: 0.66, 95% CI: 0.52–0.85), while DI-GM beneficial scores ≥6 reduced the risk by 35% compared to those with scores ≤1 (OR: 0.65, 95% CI: 0.49–0.85). RCS showed a non-linear negative trend for DI-GM (p < 0.001; nonlinear p = 0.046) and a non-linear association for DI-GM beneficial (p < 0.001; non-linear p = 0.023) with sleep disorders. Subgroup analyses confirmed the robustness of these associations among male individuals, current smokers, individuals consuming ≥12 alcoholic drinks/year, and those without hypertension, diabetes, or depression (p < 0.05). After full adjustment for covariates, mLE8 exhibited a significant mediating role in the associations of both DI-GM (14.46% mediated effect, p < 0.001) and DI-GM beneficial (12.99% mediated effect, p < 0.001) with sleep disorders. With all components of mLE8, only the nicotine exposure mediated 3.44% of the association between DI-GM and sleep disorders.ConclusionElevated DI-GM and DI-GM beneficial scores are associated with reduced incidence of sleep disorders. mLE8 mediates the associations of both DI-GM and DI-GM beneficial with sleep disorders.